Ectopic Expression of PII Induces Stomatal Closure in Lotus japonicus - Parlati, Aurora; Valkov, Vladimir T.; D'Apuzzo, Enrica; Alves, Ludovico M.; Petrozza, Angelo; Summerer, Stephan; Costa, Alex; Cellini, Francesco; Vavasseur, Alain; Chiurazzi, Maurizio (Frontiers in Plant Science, 2017)
The PII protein in plants has been associated to many different tissue specialized roles concerning the Nitrogen assimilation pathways. We report here the further characterization of L. japonicus transgenic lines overexpressing the PII protein encoded by the LjGLB1 gene that is strongly expressed in the guard cells of Lotus plants. Consistently with a putative role played by PII in that specific cellular context we have observed an alteration of the patterns of stomatal movement in the overexpressing plants. An increased stomatal closure is measured in epidermal peels from detached leaves of normally watered overexpressing plants when compared to wild type plants and this effect was by-passed by Abscisic Acid application. The biochemical characterization of the transgenic lines indicates an increased rate of the Nitric Oxide biosynthetic route, associated to an induced Nitrate Reductase activity. The phenotypic characterizazion is completed by measures of the photosynthetic potential in plants grown under greenhouse conditions, which reveal a higher stress index of the PII overexpressing plants.